2012
DOI: 10.1063/1.3670044
|View full text |Cite
|
Sign up to set email alerts
|

Geometric structure, electronic structure, and spin transition of several FeII spin-crossover molecules

Abstract: Articles you may be interested inHysteresis and change of transition temperature in thin films of Fe{[Me2Pyrz]3BH}2, a new sublimable spincrossover molecule Assessment of density functional theory for iron(II) molecules across the spin-crossover transition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Molecule (1) has stepwise spin transition with no thermal hysteresis, 11) while molecule (7) has abrupt spin transition with T ↑ = 314 K and T ↓ = 244 K resulting in wide thermal hysteresis ¦T SCO = 70 K. 12) Moreover, our previous study showed that ¦T SCO increased with ¦U of Fe II SCO complexes. 10) These results allow us to predict that designed Fe II (LX 2 ) molecules (2)(6) with ¦E in the range of [0.404, 0.443] eV should be SCO complexes with thermal hysteresis ¦T SCO in the range from 0 to 70 K. Our results clearly demonstrate that ¦E and ¦U of Fe II (LX 2 ) molecules can be tailored by variation in the axial ligand X, and the pK a constant of X is a key parameter for determining ¦E and ¦U, and thus ¦T SCO of Fe II (LX 2 ) complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecule (1) has stepwise spin transition with no thermal hysteresis, 11) while molecule (7) has abrupt spin transition with T ↑ = 314 K and T ↓ = 244 K resulting in wide thermal hysteresis ¦T SCO = 70 K. 12) Moreover, our previous study showed that ¦T SCO increased with ¦U of Fe II SCO complexes. 10) These results allow us to predict that designed Fe II (LX 2 ) molecules (2)(6) with ¦E in the range of [0.404, 0.443] eV should be SCO complexes with thermal hysteresis ¦T SCO in the range from 0 to 70 K. Our results clearly demonstrate that ¦E and ¦U of Fe II (LX 2 ) molecules can be tailored by variation in the axial ligand X, and the pK a constant of X is a key parameter for determining ¦E and ¦U, and thus ¦T SCO of Fe II (LX 2 ) complexes.…”
Section: Resultsmentioning
confidence: 99%
“…8,9) Our previous study demonstrated that ¦T SCO increased with the spin-state electrostaticenergy difference (¦U ) of Fe II SCO complexes. 10) In this paper, (6), and Him (7), in which molecules (1) and (7) have been synthesized. 1113) Their geometric structure, electronic structure, and magnetic properties have been examined in order to determine the role of ligands in tailoring SCO behavior of Fe II complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The change in spin state is associated with a change in magnetization, unit-cell volume and color; this is why materials undergoing a spin crossover transition have attracted wide interest for many potential applications, e.g. information storage, optical devices and displays (Le ´tard et al, 2003;Ksenofontov et al, 2004;Tuan, 2012;Brooker, 2015;Kahn et al, 1992;Kahn & Martinez, 1998). Recently, spin-crossover materials have been discussed as solid-state materials for caloric applications (Vallone et al, 2019;Sandeman, 2016;Romanini et al, 2021;von Ranke, 2017;Reis, 2020), as the spin crossover transition is susceptible to pressure (P).…”
Section: Introductionmentioning
confidence: 99%